The grammatical graduations of Ibn Aqil for the Quranic readings - Rasool, Kamran Ali; Awad, Sohaib Ismail; Abu Salah, Tahany Salem Mohammed (Journal of Arabic Language Sciences and Literature, 2022)
The researchers dealt with a presentation of the concept of Quranic readings, the life and efforts of Ibn Aqeel, and his grammatical graduations in terms of grammar, morphology, and language of the Quranic readings. grammatical or morphological, or confirming the views of grammarians or grammatical doctrines, or confirming Arabic dialects.